Themes of Recognition and Reification in K. S. Maniam’s Novels - Raihanah M. M.; Ruzy Suliza Hashim; Noraini Md. Yusof (Kajian Malaysia, 2011)
In the novels of the Malaysian Indian K. S. Maniam, the contestation of recognition and reification forms the central tension in the protagonists' identity development as members of a minority community in the multi-ethnic landscape of Malaya/Malaysia. Each central character's conflict lies in his/her ability/disability to balance accepting ethno-cultural recognition on the one hand and contesting the reification that the Indian ethnic group subjects him/her to on the other (subsequently championing what Michael Sandel coins an "unencumbered" sense of self – a self that is "free and independent" from "the sanctions of custom and tradition"). This paper discusses Maniam's three novels, The return, In a far country and Between lives, to ascertain the extent to which recognition and reification are important themes in the award-winning novelist's corpus. Using the conceptualisation of recognition, reification and the unencumbered self, the paper investigates how Maniam's three Indian Malaysian protagonists, Ravi, Rajan and Sumitra, like most members of minority communities who are faced with the challenges of a multi-ethnic social landscape, challenge the ethno-cultural imposition that their own ethnic community subjects them to while realising the significance of culture towards a healthy sense of selves.